The haunted house/haunted mind as a gothic trope in Mike Flanagan’s The haunting project and source texts : a comparative analysis - Botes, Christan Nancy (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.